Advances in AP2/ERF super-family transcription factors in plant. (17th August 2020) - Feng, Kai; Hou, Xi-Lin; Xing, Guo-Ming; Liu, Jie-Xia; Duan, Ao-Qi; Xu, Zhi-Sheng; Li, Meng-Yao; Zhuang, Jing; Xiong, Ai-Sheng
Abstract: In the whole life process, many factors including external and internal factors affect plant growth and development. The morphogenesis, growth, and development of plants are controlled by genetic elements and are influenced by environmental stress. Transcription factors contain one or more specific DNA-binding domains, which are essential in the whole life cycle of higher plants. The AP2/ERF (APETALA2/ethylene-responsive element binding factors) transcription factors are a large group of factors that are mainly found in plants. The transcription factors of this family serve as important regulators in many biological and physiological processes, such as plant morphogenesis, responsive mechanisms to various stresses, hormone signal transduction, and metabolite regulation. In this review, we summarized the advances in identification, classification, function, regulatory mechanisms, and the evolution of AP2/ERF transcription factors in plants. AP2/ERF family factors are mainly classified into four major subfamilies: DREB (Dehydration Responsive Element-Binding), ERF (Ethylene-Responsive-Element-Binding protein), AP2 (APETALA2) and RAV (Related to ABI3/VP), and Soloists (few unclassified factors). The review summarized the reports about multiple regulatory functions of AP2/ERF transcription factors in plants. In addition to growth regulation and stress responses, the regulatory functions of AP2/ERF in plant metabolite biosynthesis have been described. We also discussed the roles of AP2/ERF transcription factors in different phytohormone-mediated signaling pathways in plants. Genomic-wide analysis indicated that AP2/ERF transcription factors were highly conserved during plant evolution. Some public databases containing the information of AP2/ERF have been introduced. The studies of AP2/ERF factors will provide important bases for plant regulatory mechanisms and molecular breeding.